Social and geographical postulates of the formation of a new administrative-territorial structure of Ukraine - Viktoria Yavorska; Kateryna Kolomiyets (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2016)
The administrative-territorial structure (ATS) is the result of the evolution of society, the complexity of its interaction with the environment, the development of forms of its life, the formation of social and political institutions and the areas of their influence, therefore it can be considered as a socio-geographic phenomenon. Over the last decade have been developed and discussed numerous projects of the new state ATS, the new taxonomy of administrative-territorial units (ATU) and the criteria for their selection. In this article the social and geographical postulates (principles) to be used in the development of a new administrative-territorial structure. One of the requirements for the countries of Central andEastern Europe, who want to join the EU is the formally approved regionalization, so the first is the need to link the new ATS with regionalization of the state. New ATS should be based on a genetically rooted, historical and geographically-based settlement system various territorial regions – this is the second postulate. According to the third postulate – the administrative-territorial units of different levels should ideally be a territory with a socio-natural or natural-economic homogeneity and integrity. The fourth postulate states that the new state ATS should be taken into account geographic paradigm of the territorial organization of society and the concept of regional territorial structures of settlement and economy. Because society does not develop in isolation, but in the natural environment, in order to maintain its harmonious development is necessary to form natural ecological safety carcass of regions – regional ecological network. This is the fifth socio-geographic postulate. Also we should consider geoplanning peculiarities of particular area – specific spatial combinations of certain types of economic use of the territory, transport and infrastructure networks. Reliance on regional planning scheme - this is the sixth principle of construction of a new ATS. Last seventh postulate suggests that, because of historical and geographical features of settlement and economic development of the different parts ofUkraineare not same, this factor must be taken into consideration to justify a proper scheme of new state ATS.